ARRANGEMENTS OF REGIONAL TAXES AND POST REGIONAL LEVIES APPLICATION OF LAW NUMBER 1 OF 2022 CONCERNING FINANCIAL RELATIONS BETWEEN CENTRAL GOVERNMENT AND LOCAL GOVERNMENT - Pratiwi, Refi; Arisondha, Edy (PT Larva Wijaya Penerbit, 2023)
Law Number 28 of 2009 concerning Regional Taxes and Regional Levies (PDRD) has now been revoked through Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Government. Law Number 1 of 2022 is enforced in order to allocate national resources systematically The Central Government and Regional Governments in Indonesia have brought several significant changes regarding the regulation of regional taxes and regional levies. This change aims to increase the efficiency and effectiveness of regional financial management and strengthen regional autonomy This new law redefines the division of income between the central and regional governments, including the types of taxes that are a source of regional income. Regional taxes include Land and Building Tax (PBB) and Motor Vehicle Tax (PKB), while regional levies include fees for services or services provided by the regional government. Law Number 1 of 2022 is an important step in fiscal reform in Indonesia, which aims to create a better balance between the authority of the central and regional governments, while increasing efficiency and transparency in regional financial management.